Solid waste management in Korangi District of Karachi using GPS and GIS: a case study - Zeeshan, Sumayya; Shahid, Zeeshan; Khan, Sheroz; Shaikh, Faraz Ahmed (Institute of Electrical and Electronics Engineers Inc., 2018)
Solid waste management is important part of urban environmental management. Solid waste management is a chain of many factors which include proper garbage picking, organized transport, trained staff, proper channel of garbage disposition, a fully automated tracking system, and awareness in the general public about the do's and don'ts. It is equally important as any other system of survival in a city like Karachi. This paper deals with, how GIS (Geographic Information System) can be used as a decision support tool for planning waste management Total amount of waste generated in Karachi is more than 9000 tons and land filling is the most acceptable solution for waste disposal. However an inappropriate selected site can lead to many environmental, economical and ecological impacts. For the selection of landfill or final disposal site of waste many factors were kept in consideration. The aim of this paper is to select an appropriate site for the landfill or final waste disposal site of waste for District Korangi, Karachi. Many factors were kept under consideration like water bodies, road distance and land use. The designed models have been implemented on the data obtained from the satellite images for the analysis in ARCGIS software. Weighted overlay analysis, a decision making tool was used for the selection of suitable site. The results suggest some modification in the existing system which is expected to reduce the waste management workload to a certain extent.